2011
DOI: 10.2134/agronj2011.0129
|View full text |Cite
|
Sign up to set email alerts
|

Location, Variety, and Seeding Rate Interactions with Soybean Seed‐Applied Insecticide/Fungicides

Abstract: Cool conditions aft er soybean [Glycine max (L.) Merr.] planting may increase soil pest incidence and reduce emergence. Fieldscale studies were conducted in 2009 and 2010 at three locations in New York on two varieties at four seeding rates (272,000, 346,000, 420,000, and 490,000 seeds ha -1 ) with and without seed-applied insecticide/fungicides to determine if treated seed enhances plant establishment, allowing for lower seeding rates for maximum yield and partial return. Plant density and yield had location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 32 publications
3
21
1
Order By: Relevance
“…Looking further into the 2013 results indicated the addition of thiamethoxam (CM) increased yield by 4% (175 kg ha −1 ) over the UTC and by 3.6% (145 kg ha −1 ) over its fungicide only counterpart, AM (Table 5). This yield increase over AM is consistent with the 2011–2012 results in the current study, and the 4% increase over the UTC is identical to results from Gaspar et al (2014) and Cox and Cherney (2011). However, the addition of the nematicide abamectin to CM, which results in CMA (4235 kg ha −1 ), did not increase yield any further (Table 5).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Looking further into the 2013 results indicated the addition of thiamethoxam (CM) increased yield by 4% (175 kg ha −1 ) over the UTC and by 3.6% (145 kg ha −1 ) over its fungicide only counterpart, AM (Table 5). This yield increase over AM is consistent with the 2011–2012 results in the current study, and the 4% increase over the UTC is identical to results from Gaspar et al (2014) and Cox and Cherney (2011). However, the addition of the nematicide abamectin to CM, which results in CMA (4235 kg ha −1 ), did not increase yield any further (Table 5).…”
Section: Resultssupporting
confidence: 89%
“…As seed costs increase, the use of seed treatments may allow producers to lower their seeding rates and therefore reduce the cost of soybean seed per hectare. This is confirmed by Gaspar et al (2014) and Cox and Cherney (2011) who reported that seeding rates should be lowered by approximately 50,000 seeds ha −1 to maximize partial profit when a fungicide/insecticide seed treatment was used compared to no seed treatment. Commodity prices have a direct relation to the profitability of a seed treatment and ultimately producers are more interested in products that are cost effective, implying they are able to increase yield enough to increasing profitability (Marra et al, 2003; Pannell et al, 2000).…”
supporting
confidence: 55%
See 2 more Smart Citations
“…The location × seed treatment yield interaction was not associated with planting equipment at different locations, as indicated by a positive yield response to the rhizobia–biological–fungicide–insecticide seed treatment at a grain drill (Seneca County) and a row crop location (Yates County) and no response at a grain drill (Livingston County) and a row crop location (Tomkins County). Other researchers have also observed an inconsistent yield increase with the use of fungicide and/or insecticide seed treatments, despite increases in early plant populations (Bradley et al, 2001; Poag et al, 2005; Murillo‐Williams and Pedersen, 2008; Schulz and Thelen, 2008; Cox and Cherney, 2011b; Esker and Conley, 2012). The addition of the biological compound PPST 2030 to fungicide and/or insecticide seed treatments did not reduce the inconsistent yield response to soybean seed treatments in this study.…”
Section: Resultsmentioning
confidence: 97%